Human blood lipid profiles after dietary supplementation of different omega 3 ethyl esters formulations - Donnarumma, Danilo; Di Salle, Anna; Micalizzi, Giuseppe; Vento, Federica; La Tella, Roberta; Iannotta, Pasquale; Trovato, Emanuela; Melone, Mariarosa Anna Beatrice; Rigano, Francesca; Donato, Paola; Mondello, Luigi; Peluso, Gianfranco (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2023)
The validity of omega 3 fatty acids (ω3 FAs), mainly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), as dietary supplements has been widely proved. It's well known in fact, that they protect against cardiovascular diseases, reduce the levels of triacylglycerides (TAGs) and cholesteryl esters (CEs) in blood, and have anti-inflammatory activity. For these reasons, in the last few years the production of dietary supplement containing ω3 has increased significantly. In this context, the possibility to obtain ω3 and other high value molecules from alternative sources as fish waste, in accordance with the principles of circular economy, becomes an enormous attractive. In addition, the opportunity of creating new products, with greater health benefits, represents an interesting challenge. The current study was focused on the extraction of ω3 fatty acids and peptides from tuna waste industry, to realize a new dietary supplement. To this purpose, a supercritical fluid extraction (SFE) method was developed to separate, isolate, and enrich the different fractions subsequently used to produce an innovative formulate. The obtained supplement was characterized in terms of fatty acids esterified ester (FAEE) composition by gas chromatography (GC) coupled to both flame ionization detection (FID) and mass spectrometry (MS), and content of heavy metals by inductively coupled plasma-mass spectrometry (ICP-MS). The effects of ω3 supplementation on metabolism and circulating lipid profiles was tested on 12 volunteers and assessed by GC-FID analysis of whole blood collected on paper support (Dried Blood Spot, DBS) at the beginning of the study and after thirty days. The results of plasma fatty acids levels after 30 days showed a significant decrease in the ω6/ω3 ratio, as well as the saturated/polyunsaturated fatty acids (SFA/PUFA) ratio, compared to subjects who took the ω3 ethyl esters unformulated. The novel formulated supplements proved to be extremely interesting and promising products, due to a significant increase in bioavailability, that makes it highly competitive in the current panorama of the nutraceutical industry.